Respuesta :
Answer:
(x-2)(x+6)=0; x=2, x=6
Step-by-step explanation:
Assuming you meant x^2
Easy factoring here.
x^2+4x-12=0
What multiples to get -12 and adds to get +4
-2 and 6
(x-2)(x+6)=0; or x=2, x=-6
Answer:
(x + 6)(x - 2)
Step-by-step explanation:
Find factors of x² and -12 that, when FOILed, would give you 4x in the middle.
In this case, use the factor 6 & -2:
x² + 4x - 12
x 6
x - 2
(x + 6)(x - 2) is your answer.
Check. Use the FOIL method:
FOIL =
First, Outside, Inside, Last
(x)(x) = x²
(x)(-2) = -2x
(6)(x) = 6x
(6)(-2) = -12
Combine like terms:
x² (-2x + 6x) - 12 = x² + 4x - 12
~